"Effect of Coagulants on Electrochemical Process for Phosphorus Removal from Activated Sludge Effluent" - AR Mesdaghinia; D Rabbani; S Nasseri; F Vaezi (Tehran University of Medical Sciences, 2003)
According to Environmental Protection Organization of Iran, maximum permissible concentration of residual phosphorus in treated municipal wastewater is 1 mg /l-P. The total average phosphorus concentration in raw municipal wastewater is about 8 mg / l; about 70 percent of the incoming phosphorus normally is discharged with secondary treatment plant effluents. In this research, the role of adding different kinds of coagulants on phosphorus removal efficiency of an electrochemical process was investigated. The research is a bench scale experimental type using batch system for elec. process with direct current. Samples were collected from an extended aeration effluent. The used electrode was steel type and its total effective area was 336 cm2. In each run 1500 ml of sample was placed in an electrolytic cell equipped with magnetic stirrer. The results show that phosphorus removal efficiency increases by increasing of DC and reaction time. Minimum rate of current/percentage of removal was obtained for 0.6amp current and under the same conditions minimum rate of reaction time/percentage of removal was provided in 15 min. In 6min reaction time and 0.6amp current, adding poly aluminum chloride (PAC) up to about 27 mg/l could improve the efficiency up to about 50%. But under the same condition, similar results were not observed in 12min reaction time. Besides, adding alum or ferrous sulfate showed similar behavior to PAC. Electrochemical treatment without addition of coagulants and thereby without any changes on the primary characteristics of the sample can remove the phosphorus up to about 93%. But in the case of sufficient reaction time for electrochemical process, adding coagulants can not improve the efficiency and in comparison to a chemical precipitation alone, the use of electrochemical treatment can not reduce the required doses of coagulants in short reaction time.